The Effectiveness of Biochar, Compost, and Natural Phosphate in Improving Soil Quality in Oil Palm Plantations - Sunarti; Endriani; Farni, Yulfita; Listyarini , Diah; Fuadi, Najla Anwar (Akta Agrosia, 2024)
Oil palm cultivation is increasingly carried out on suboptimal land, such as Ultisols. Application of ameliorant such as biochar and compost may be chosen as an alternative to solve the problem occurred on this sub optimal soil. This study aims to determine the optimal dosage of a mixture of oil palm empty fruit bunch (EFB) biochar, poultry manure compost, and Rock Phosphate (RP) to enhance soil quality and support the growth of one-year-old oil palm plants. The study was conducted over six months in a one-year-old oil palm plantation located in Panca Mulya Village. A randomized Complete Block Design (RCBD) was employed with the aplication of biochar, compost, and rock phosphate (RP = Togo Rock Phosphate, 33.5% P₂O₅) in the following treatments: P0 = control (no treatment); P1 = biochar 20 tons.ha-1 + RP 200 kg.ha-1; P2 = biochar 10 tons/ha + compost 10 tons.ha-1 + RP 200 kg.ha-1; P3 = compost 20 tons.ha-1 + RP 200 kg.ha-1; P4 = biochar 20 tons.ha-1 +compost 10 tons.ha-1 + RP 200 kg.ha-1; P5= biochar 10 tons.ha-1 + compost 20 tons.ha-1 + RP 200 kg.ha-1. Results indicated that the application of biochar, compost, and RP, whether individually or in combination, enhanced oil palm growth compared to the control. The application of biochar and compost improved soil physical properties, increased soil organic matter content, total pore space, available water content, reduced bulk density, soil penetration resistance, and promoted oil palm growth. The best treatment was found to be 10 tons.ha-1 biochar + 20 tons.ha-1 compost + 200 kg.ha-1 RP. Keywords: ameliorant, empty fruit bunch, soil quality